2020
DOI: 10.23960/jbekh.v7i2.150
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Lichen Diversity in Gunung Halimun Salak National Park

Abstract: Lichen is an associated organism between fungi and algae. The research of lichen in Indonesia still inadequate, especially on the island of Java. Gunung Halimun Salak National Park is one of conservation area in West Java. The diversity of lichen in this area has never been reported. This study aims to provide preliminary information of lichen diversity in Gunung Halimun Salak National Park. This research was conducted in October 2019. All of the lichen specimens were carried out along the main road of Gunung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Data from Herbarium Bogoriense Bogor records that lichen biodiversity in Indonesia is about 40,000 species (Suwarso, 1995). The high lichen biodiversity in tropical areas is due to diverse and supporting environmental factors (Fastanti et al, 2020). Opportunities for lichen study are open since only a few researchers focus on lichen study (Ramadhanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Herbarium Bogoriense Bogor records that lichen biodiversity in Indonesia is about 40,000 species (Suwarso, 1995). The high lichen biodiversity in tropical areas is due to diverse and supporting environmental factors (Fastanti et al, 2020). Opportunities for lichen study are open since only a few researchers focus on lichen study (Ramadhanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on lichen diversity in PPKA Bodogol West Java are limited. Several reported studies on lichen in the Java area include those in the Geopark area Cileteuh Sukabumi, West Java (Permatasari et al, 2016), Kamojang, West Java (Kusmoro et al, 2018), Great Forest Park, East Java (Jannah et al, 2019), Jatinangor, West Java (Kusmoro et al, 2019), and Mount Halimun Salak National Park, West Java (Fastanti et al, 2020). However, only a small number of studies on lichen biodiversity are reported in the area of Mount Gede Pangrango National Park, especially in PPKA Bodogol.…”
Section: Introductionmentioning
confidence: 99%